Nanometer Precision Measurement of Submicron Fibers via Seeded Four-Wave-Mixing - Hammer, Jonas; Haupl, Daniel R.; Russell, Philip St. John; Joly, Nicolas (Conference Proceedings - Lasers and Electro-Optics Society Annual Meeting-LEOS, 2020)
We report non-destructive measurement of the diameter of submicron air-clad waveguides to nanometer precision, based on parametric amplification of a broadband seed signal. Ultrashort pump and seed pulses allow the diameter to be longitudinally resolved.
CRIS-Team Scopus Importer:2020-10-09